2020
DOI: 10.3892/br.2020.1304
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline cooperatively exerts an anti‑inflammatory effect on synovial cells with glucosamine and N‑acetylglucosamine

Abstract: The aim of the present study was to evaluate the anti-inflammatory effects of citrulline (Cit), glucosamine (GlcN) and N-acetylglucosamine (GlcNAc) on synovial cells, which are primarily involved in inflammatory joint diseases. The combined effect of Cit, GlcN and GlcNAc on synovial cell inflammation was assessed by measuring IL-1β-induced IL-6 production. GlcN and GlcNAc (0.5 mM each) alone did not suppress IL-6 production, whereas Cit (0.5 mM) did significantly suppress IL-6 production. Furthermore, the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Diet with high methionine has been shown to attenuate arthritic severity in rats ( 26 ). Both citrulline and arginine have anti-inflammatory properties and arginine is in phase 2 trial in treatment of RA ( 27 , 28 ). Reduced levels of both arginine and citrulline suggest alterations in microbial diversity with compensatory microbial changes.…”
Section: Discussionmentioning
confidence: 99%
“…Diet with high methionine has been shown to attenuate arthritic severity in rats ( 26 ). Both citrulline and arginine have anti-inflammatory properties and arginine is in phase 2 trial in treatment of RA ( 27 , 28 ). Reduced levels of both arginine and citrulline suggest alterations in microbial diversity with compensatory microbial changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the serum levels of this inflammatory biomarker were significantly reduced in the l -CIT group. Some in-vitro and in-vivo studies indicated that the l -CIT supplementation reduces serum inflammatory cytokines such as IL-6 [ 51 53 ]. Furthermore, a clinical study has supported the IL-6 lowering effect of CIT (10 g/day) for ten days [ 54 ]; while, Breuillard et al [ 55 ] reported a positive relationship between IL-6 productions and CIT concentration associated to a decrease in tumor necrosis factor-alpha (TNF-α) production in the peritoneal macrophages in obese diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…l -CIT supplementation had no significant effect on serum MCP-1and TLR-4 levels, whereas the serum TLR-4 levels were significantly reduced in the l -CIT group compared to the baseline.To the best of our knowledge, we could not find a randomized controlled trial assessing meta-inflammatory biomarkers in T2D patients. However, the effects of the l -CIT or watermelon component, as a source of l -CIT, on TLR-4 and MCP-1 were studied in some animal studies [ 24 , 36 , 51 , 56 ]. For example, Jegatheesan et al [ 24 ] reported that the administration of 1 g/kg/d l -CIT in nonalcoholic fatty liver disease (NAFLD) rats reduced TLR4 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have been investigating the anti-inflammatory effects of various functional food materials, such as glucosamine, citrulline, methionine, and chondroitin sulfate, on IL-6 and IL-8 production by IL-1β-stimulated synovial cells (22,23), and revealed that these materials inhibit cytokine production by suppressing signaling molecules, including nuclear factor (NF)-κB, extracellular signal regulated kinases (ERK)1/2, and p38 mitogen-activated protein kinase (MAPK). However, the anti-inflammatory effects of isoflavones (daidzein, genistein, and glycitein) on inflammatory cytokine production by IL-1β-stimulated synovial cells have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%